Módulo para la simulación de matrícula por asignatura en la carrera de Ingeniería en Sistemas/Computación - Bermeo Armijos, Johnney Javier (2023)
In the present, the Systems/Computer Engineering Career (SCEC) belonging to the Faculty of Energy, Industries and Non-Renewable Natural Resources (FEINRNR) of Universidad Nacional de Loja (UNL), the enrollment application process by subject is carried out manually, since there is no tool, application or official service that facilitates the calculation of the process in matter, resulting in an inefficient process in terms of time for students and administrative staff. Based on this fact, the actual degree work (DW), called Module for the simulation of enrollment by Subject in the Systems/Computer Engineering Career, was analyzed and developed as a software solution for the automation of the activities that are part of the internal process of enrollment application. The analysis, design and implementation of this software solution aims to systematize the application process for second and third enrollment at CISC, taking into consideration the criteria of prerequisites for each subject, percentage of valid credits for each cycle, crossing schedules of subjects in each parallel and cycle, established in the Organic Statue and General Guidelines for the application of the recovery test and the registration of second and third enrollment of the UNL and answer the research question: Would the automation of the module for the stimulation of enrollment application by subject of the Systems/Computer Engineering career of Universidad Nacional de Loja, optimize the time of people involved on it? Using the BPM:RAD methodology, the information obtained from the results of the interviews and the analysis of the literature review, the main activities, tasks, and actors involved in the enrollment application process were identified and defined, and with these results the current process diagram was developed, and an automated model was proposed. Subsequently, the UML-Based Web Engineering (UWE) methodology and the Enterprise Resource Planning (ERP) system called ODOO were used to develop the system. Finally, an implementation plan was generated and defined based on the modification of the method proposed by Pablo González Fernández. Keywords: [BPMN; Odoo ERP; Implementation plan; Subject Matriculation Application].